2012
DOI: 10.1159/000336273
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Persistent Cystoid Macular Edema due to Central Retinal Vein Occlusion in a Vitrectomized Eye following Intravitreal Implant of Dexamethasone 0.7 mg

Abstract: We report the case of a 62-year-old woman with a history of vitreoretinal surgery for vitreous hemorrhage secondary to central retinal vein occlusion (CRVO). Because of the persistence of macular edema (ME), she received 2 intravitreal injections of bevacizumab 0.5 mg (Avastin®, Genentech/Roche) three months after vitrectomy, without functional or anatomical improvement. Six months after vitrectomy, she therefore received an intravitreal implant of dexamethasone 0.7 mg (Ozurdex®). An improvement in her best-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Sustained-release corticosteroids have the potential to reduce the need for frequent intraocular injections in vitrectomized eyes. However, thus far, only very few studies have attempted to investigate the effect of sustained-release steroid implants in persistent CME following vitrectomy [7,16,18,20] . In a series of 5 patients, Taney et al [17] showed that DEX had a beneficial effect on persistent macular edema after vitrectomy with epiretinal membrane peeling, although treatment frequently required repeated injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained-release corticosteroids have the potential to reduce the need for frequent intraocular injections in vitrectomized eyes. However, thus far, only very few studies have attempted to investigate the effect of sustained-release steroid implants in persistent CME following vitrectomy [7,16,18,20] . In a series of 5 patients, Taney et al [17] showed that DEX had a beneficial effect on persistent macular edema after vitrectomy with epiretinal membrane peeling, although treatment frequently required repeated injections.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (DEX) intravitreal implant (Ozurdex ® , Allergan, Inc., Irvine, CA, USA and Allergan Pharmaceuticals, Ireland) has been shown to reduce central retinal thickness (CRT) and improve best-corrected visual acuity (BCVA) in patients with macular edema of various etiologies including noninfectious uveitis, diabetes mellitus, and retinal vein occlusion [8][9][10][11][12][13][14][15] . Over the past years, several small case series and anecdotal reports have strengthened the hypothesis that intravitreal steroid implants may be effective in the treatment of refractory CME in vitrectomized eyes [16][17][18][19][20] . However, to date there are no large studies evaluating the efficacy and safety of intravitreal sustained-release steroid implants for the management of CME following vitrectomy and membrane peeling.…”
mentioning
confidence: 99%
“…Given the results of the GENEVA trials, some advocate use of the implant for patients with a relatively short duration of macular edema [48]. Others have suggested that the dexamethasone implant may be useful for less frequent occurrences of macular edema secondary to RVO, such as those occurring in postvitrectomized eyes with CRVO, and those with long-standing BRVO and chronic edema [49, 50]. …”
Section: Treatment Of Inflammation In Rvomentioning
confidence: 99%
“…Recently, a sustained-release dexamethasone implant (Ozurdex ® ) proved to be effective for the treatment of macular edema secondary to a variety of underlying diseases with a potentially lower rate of adverse events [7, 8, 9]. We report a case of rhegmatogenous retinal detachment with a high risk of PVR treated with episcleral surgery and an intravitreal dexamethasone 0.7-mg implant (Ozurdex).…”
Section: Introductionmentioning
confidence: 99%